2020
DOI: 10.3390/ijerph17239046
|View full text |Cite
|
Sign up to set email alerts
|

INSIDE Project: Individual Air Pollution Exposure, Extracellular Vesicles Signaling and Hypertensive Disorder Development in Pregnancy

Abstract: Hypertensive disorders are common complications during pregnancy (HDP) with substantial public health impact. Acute and chronic particulate matter (PM) exposure during pregnancy increases the risk of HDP, although the underlying molecular mechanisms remain unclear. Extracellular vesicles (EVs) may be the ideal candidates for mediating the effects of PM exposure in pregnancy as they are released in response to environmental stimuli. The INSIDE project aims to investigate this mechanism in pregnancy outcomes. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…This aim will be achieved by considering two methods for environmental exposure, thus maximizing the probability of assigning accurate exposure values to our population. Both approaches have proved their soundness in similar settings, as documented in previous studies on health effects of air pollution exposure [ 44 , 46 , 47 , 48 ]. In particular, the assignment of personal exposures based on residential address using daily pollutant levels at a 1 × 1 km resolution represents the best compromise between spatial and temporal resolution that we can currently achieve when considering our entire regional territory.…”
Section: Discussionmentioning
confidence: 63%
“…This aim will be achieved by considering two methods for environmental exposure, thus maximizing the probability of assigning accurate exposure values to our population. Both approaches have proved their soundness in similar settings, as documented in previous studies on health effects of air pollution exposure [ 44 , 46 , 47 , 48 ]. In particular, the assignment of personal exposures based on residential address using daily pollutant levels at a 1 × 1 km resolution represents the best compromise between spatial and temporal resolution that we can currently achieve when considering our entire regional territory.…”
Section: Discussionmentioning
confidence: 63%
“…In addition, EVs released upon PM exposure provoke disease outcomes in the molecular mechanism. The INSIDE study identified the health impacts of PM exposure during pregnancy and hypertensive disorder development, demonstrating a link between PM exposure and EVs, such as biomarkers and mediators of cardiovascular disease [114]. Moreover, another study demonstrated that PM 2.5 is associated with endothelial dysfunction and increases cardiovascular morbidity and mortality risk due to vascular aging.…”
Section: Extracellular Vesicles Particulate Matter and Age-related Di...mentioning
confidence: 99%
“…Numerous projects link human disorders to air pollution, we report here only a few that are representative of the wide variety of impacts. In pregnancy (Ferrari et al, 2020), in asthma and lung function (Rusconi et al, 2011) and others that indirectly impact the human body. NO2 specifically was found to be linked to paediatric asthma also in cities with NO2 emissions lower then the guideline from the WHO (Achakulwisut et al, 2019).…”
Section: Air Pollution Effect On Healthmentioning
confidence: 99%